Segmental Duplications as a Complement Strategy to Short Tandem Repeats in the Prenatal Diagnosis of Down Syndrome - Mohammad Reza Miri; Jamileh Saberzadeh; Abbas Behzad Behbahani; Mohammad Bagher Tabei; Mohsen Alipour; Majid Fardaei (Iranian Journal of Medical Sciences, 2019)
Background: Quantitative fluorescence-polymerase chain reaction (QF-PCR) is an inexpensive and accurate method for the prenatal diagnosis of aneuploidies that applies short tandem repeats (STRs) as a chromosome-specific marker. Despite its apparent advantages, QF-PCR is not applicable in all cases due to the presence of uninformative STRs. This study was carried out to investigate the efficiency of a method based on applying segmental duplications (SDs) in conjunction with STRs as an alternative to stand-alone STR-based QF-PCR for the diagnosis of Down syndrome. Methods: Fifty amniotic fluid samples from pregnant women carrying Down syndrome fetuses, 9 amniotic fluid samples with 1 or without any informative STR marker (inconclusive), and 100 normal samples were selected from Shiraz, Iran, between October 2015 and December 2016. Analysis was done using an in-house STR-SD-based multiplex QF-PCR and the results were compared. Statistical analysis was performed using MedCalc, version 14.Results: All the normal, Down syndrome, and inconclusive samples were accurately identified by the STR-SD-based multiplex QF-PCR, yielding 100% sensitivity and 100% specificity. Karyotype analysis confirmed all the cases with normal or trisomic results.Conclusion: The STR-SD-based multiplex QF-PCR correctly identified all the normal and trisomy 21 samples regardless of the absence of informative STR markers. The STR-SD-based multiplex QF-PCR is a feasible and particularly useful assay in populations with a high prevalence of homozygote STR markers.